Réponses

2013-11-16T12:21:32+01:00
A) 3(x-2)+2x
   3x-6+2x=5x-6
b) -3(x+2)+5(x-3)
   -3x-6+5x-15=2x-21
c)(-7+a)(-4)+6(11-a)+5a
  28-4a+66-6a+5a=-5a+94
d) -2(4b-5)-(2+3b)+3(4b-1)
  -8b+10-2-3b+12b-3=b+5
Meilleure réponse !
2013-11-16T12:21:50+01:00
a = 3 ( x - 2 ) + 2x
= 3 * x + 3 * (-2) + 2x
= 3x - 6 + 2x
= 5x - 6

b = 
-3 ( x + 2 ) + 5 ( x - 3 )
= -3 * x - 3 * 2 + 5 * x + 5 * (-3)
= -3x - 6 + 5x - 15
= 2x -21

c = 
( -7 + a ) (-4) + 6 ( 11 - a ) + 5a
= -4 * (-7) - 4 * a + 6 * 11 + 6 * (-a) + 5a
= 28 - 4a + 66 - 6a + 5a
= 94 -5a

d = 
-2 ( 4b - 5 ) - ( 2 + 3b ) + 3 ( 4b - 1 )
= -2 * 4b - 2 * (-5) - 2 - 3b + 3 * 4b + 3 * (-1)
= -8b + 10 - 2 - 3b + 12b - 3
= 1b + 5